2001
DOI: 10.1071/wf01022
|View full text |Cite
|
Sign up to set email alerts
|

Estimating live fine fuels moisture content using meteorologically-based indices

Abstract: Field measurements of moisture content of several fine fuels (shrub vegetation and live foliage) were performed in Central Portugal and in Catalunya (NE Spain) for 1–10 years. Seasonal and interannual variation of live fine fuels of several species in two regions of the Iberian Peninsula are analysed. The species were grouped in three sets according to their relatively high, intermediate or low seasonal variability. Meteorological data from nearby stations were collected in each study area and used in the eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
85
2
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(97 citation statements)
references
References 9 publications
7
85
2
3
Order By: Relevance
“…It is calculated from daily rainfall and air temperature during and prior to the fire day. In the Mediterranean, DC has also been related with the moisture content of living shoots of plants, although the responsiveness of living fuel to weather can greatly vary among species according to their ability to dynamically adjust their water status (Viegas et al, 2001 Fig. 1; Météo-France).…”
Section: Discussionmentioning
confidence: 99%
“…It is calculated from daily rainfall and air temperature during and prior to the fire day. In the Mediterranean, DC has also been related with the moisture content of living shoots of plants, although the responsiveness of living fuel to weather can greatly vary among species according to their ability to dynamically adjust their water status (Viegas et al, 2001 Fig. 1; Météo-France).…”
Section: Discussionmentioning
confidence: 99%
“…Viegas et al (1999) validated several such indices in the Mediterranean against observed fire occurrence, with the Canadian Fire Weather Index (FWI, van Wagner 1987) amongst the best performers. Viegas et al (2001) demonstrated that in summer, the slow response of live fine fuel moisture content to meteorological conditions is well described by the Drought Code subcomponent of the FWI system. The FWI model is non-dimensional, based on physical processes and has been used in many different locations, so seems a sensible basis for exploring the mechanisms of fire risk change.…”
Section: Introductionmentioning
confidence: 99%
“…This parameter was then incorporated into fire spread models in dead fuels [2], and later these models were expanded to include mixtures of living and dead fuels [3,4]. Live fuel moistures are generally an order of magnitude higher than dead fuel moistures, but during this early model development it was assumed that fuel moisture content alone could sufficiently describe the ignition and spread behavior differences between live and dead fuels; this assumption still persists in most live fuel flammability research [5][6][7]. Essentially, live fuels were simply assumed to be very wet dead fuels and nothing more.…”
Section: Introductionmentioning
confidence: 99%